2000
DOI: 10.1111/j.1601-0825.2000.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of lactobacilli isolated from healthy subjects

Abstract: OBJECTIVE: Lactobacilli are considered cariogenic micro‐organismS. As oral species of lactobacilli have not been thoroughly described, the aim of this work was to isolate and identify these organisms from teeth, tongue, saliva and gum of healthy patients and to describe some of their surface properties. SUBJECTS: Forty‐four subjects from Tucumán, Argentina, with D, d and M, m indices equal to 0. MATERIALS AND METHODS: Samples were obtained from different areas of the oral cavity. Microorganisms were cultured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
3
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 22 publications
5
65
3
1
Order By: Relevance
“…The majority of the strains isolated from the three ecosystems were shown to be nonhydrophobic. These results are diVerent from those obtained in strains isolated from human vaginal tract [18], or oral cavity [4]. These diVerences could indicate some characteristic of speciWc ecological niches or tracts, but further studies should be performed to increase the knowledge in the speciWc bovine host.…”
Section: Discussioncontrasting
confidence: 80%
“…The majority of the strains isolated from the three ecosystems were shown to be nonhydrophobic. These results are diVerent from those obtained in strains isolated from human vaginal tract [18], or oral cavity [4]. These diVerences could indicate some characteristic of speciWc ecological niches or tracts, but further studies should be performed to increase the knowledge in the speciWc bovine host.…”
Section: Discussioncontrasting
confidence: 80%
“…Although we did not determine the Lactobacillus species found in the children and their mothers, it is likely that these belong to common commensal groups such as L. salivarius, which constitute part of the normal oral flora [Colloca et al, 2000]. The association of natural birth with LB colonization found in the present study extends the results of previous studies that showed that maternal transmission of LB to her infant through natural birth is possible [Tannock et al, 1990;Matsumiya et al, 2002].…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, a recent study showed that soft-tissue colonization by cariogenic streptococcal species occurs at a greater rate than colonization of the teeth [Gizani et al, 2009]. Lactobacillus species have also been reported to preferentially adhere to the mucosa of the tongue and gingival mucosa compared to other sites [Michalek et al, 1981;Colloca et al, 2000]. Additionally, although there are several crosssectional studies on the prevalence of Lactobacillus species in children at various ages [Alaluusua, 1993;Bokhout et al, 1996;Aguilera Galaviz et al, 2005], there have been few longitudinal studies on the colonization of Lactobacillus species in predentate children, as previous investigations have largely focused on children with erupted teeth [Teanpaisan et al, 2007].…”
mentioning
confidence: 99%
“…This characteristic could promote the ability of the bacterial surface hydrophobicity to adapt to environmental changes. [8][9][10][11] The best known determinants of cariogenicity in lactobacilli are their capacity to produce acids and their ability to grow and survive in an acidic environment. [12][13][14][15] The presence of S. mutans and Lactobacillus acidophilus in dental biofilm has been used as an indicator of cariogenic biofilm.…”
mentioning
confidence: 99%